Guidance note for peace-informed programming at the Green Climate Fund: Forest and Land Use - Scartozzi, Cesare M.; Caroli, Giulia; Sarzana, Carolina; Läderach, Peter R.D.; Pacillo, Grazia; Hyslop, Daniel; Hahn, Andreas Luis; Azar, Elio; Nicatore, Giorgia; Brown, Oliver; Hassamal, Komal; Ehmsen, Simon (2023)
Land has historically been a focal point of conflict, especially in Fragile and Conflict-affected Settings (FCS), where disputes over forests and land use often intersect with broader socio-political dynamics, including unfair resource allocation, marginalization, and governance challenges. Factors such as climate change, population growth, and urbanization are anticipated to intensify these conflicts in the coming decades. While projects related to forests and land use aim to address these challenges, they can inadvertently exacerbate tensions, especially if they limit resource access, have weak governance, or marginalize local stakeholders. However, with a conflict-sensitive approach, such projects can promote peace by ensuring equitable land access, fostering sustainable resource management, solidifying land rights, and building trust through community engagement and knowledge-sharing.